Pengembangan Media Pembelajaran Pada Mata Kuliah Analisa Struktur Di Jurusan Pendidikan Teknik Sipil Dan Perencanaan Universitas Negeri Makassar - Sari, Fajrianti; Pertiwi, Nurlita; Natsir, Taufiq (Jurnal Pendidikan Teknik Sipil dan Arsitektur, 2023)
Study this aim for developing learning media eye Structural Analysis course special static portal material no of course with method style . Subject in study this is students who program eye Structural Analysis course , and the object of research this is a learning medium interactive in the form of percentage materials and examples matter . Research results show that the media developed " Already " effective ” based on the assessment that has been carried out by expert validators . Validator experts assess that the developed media already valid with the average percentage obtained is 96.36% which includes in "Very Valid" category . After tested small to 15 students obtained the average percentage of the 3 aspects assessed which is 85.17% which indicates the quality of the media created including “Very Good ” category with Qualification “Very Valid”